UPAYA MENINGKATKAN KEAKTIFAN DAN PRESTASI BELAJAR MATEMATIKA MELALUI PEMBELAJARAN TEAM ASSISTED INDIVIDUALIZATION PADA SISWA KELAS VII B SMP NEGERI 1 CILACAP TAHUN AJARAN 2013/2014 - Era Hestiningrum; A. A Sujadi (UNION: Jurnal Ilmiah Pendidikan Matematika, 2015)
The aim of this research was to describe about teaching learning process using Cooperative Team Assisted Individualization (TAI) to increase student’s active and study result to the VII B grade student’s at SMP Negeri 1 Cilacap. The hypothesis of this research was applying TAI could increase student’s active and student’s study result. This research was Classroom Action Research. The research result showed that after applying TAI in teaching learning process, the student’s active increasing. Before this research the students were passive to listen to the teacher’s explanation but after this research the students were more active to ask and discuss in group. Means student’s score increased, first 65,17 score, increasing in first cycle was 69,33 and increasing second cycle was 78,13. From the result above, it showed that TAI could increase student’s active and study result.